Pengaturan Kehamilan Dan Keadaan Gizi Bayi - Rossi Sanusi, Rossi Sanusi (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1981)
This study examined the effect of parity, maternal age, and interval between pregnancies on body- weights of ill infants of a rural village in Central Java during the first 12 months of life. With a few exceptions, differences in these pregnancy factors were not accompanied by differences in body-weight growth.The pregnancy data were dichotomized at 2, 3, and 4 pregnancies for parity, at 35 years for maternal age, and at 17 months for pregnancy interval.Key Words: parity - birth intervals - age-specific birth rate - infant morbidity - infant nutrition